Socially Responsible Project Accounting: A Systematic Literature Review - Olga ZUCZEK (Communications of International Proceedings, 2024)
The growing emphasis on sustainable development has driven the incorporation of social and environmental considerations into project management. Nonetheless, the current literature lacks comprehensive studies examining the role of socially responsible accounting in the assessment of sustainable projects. This study seeks to address this gap by investigating how socially responsible accounting—particularly in terms of social and environmental costs—can enhance decision-making in sustainable project management. Through a review of existing frameworks and case studies, this research explores the contribution of socially responsible accounting to the evaluation of sustainable projects. The findings indicate that traditional accounting practices fall short in supporting sustainable project evaluations, whereas socially responsible accounting provides a more comprehensive perspective, enabling organizations to make better-informed decisions. This study underscores the importance of integrating broader sustainability metrics into accounting practices to more effectively align with the objectives of sustainable development.
Keywords: sustainable development; sustainable project management; socially responsible accounting